The effects of high intensity interval training in normobaric hypoxia on aerobic capacity in basketball players - Czuba, M.; Zajac, A.; Maszczyk, A.; Roczniok, R.; Poprzecki, S.; Garbaciak, W.; Zajac, T. (Journal of Human Kinetics, 2013)
The aim of the present study was to evaluate the efficacy of 3-week high intensity interval training in normobaric hypoxia (IHT) on aerobic capacity in basketball players. Twelve male well trained basketball players, randomly divided into a hypoxia (H) group (n=6; age: 22±1.6 years; VO2max: 52.6±3.9 ml/kg/min; body height - BH: 188.8±6.1 cm; body mass - BM: 83.9±7.2 kg; % of body fat - FAT%: 11.2±3.1%), and a control (C) group (n=6; age: 22±2.4 years; VO2max: 53.0±5.2 ml/kg/min; BH: 194.3 ± 6.6 cm; BM: 99.9±11.1 kg; FAT% 11.0±2.8 %) took part in the study. The training program applied during the study was the same for both groups, but with different environmental conditions during the selected interval training sessions. For 3 weeks, all subjects performed three high intensity interval training sessions per week. During the interval training sessions, the H group trained in a normobaric hypoxic chamber at a simulated altitude of 2500 m, while the group C performed interval training sessions under normoxia conditions also inside the chamber. Each interval running training sessions consisted of four to five 4 min bouts at 90% of VO2max velocity determined in hypoxia (vVO2max-hyp) for the H group and 90% of velocity at VO2max determined in normoxia for the group C. The statistical post-hoc analysis showed that the training in hypoxia caused a significant (p<0.001) increase (10%) in total distance during the ramp test protocol (the speed was increased linearly by 1 km/h per 1min until volitional exhaustion), as well as increased (p<0.01) absolute (4.5%) and relative (6.2%) maximal workload (WRmax). Also, the absolute and relative values of VO2max in this group increased significantly (p<0.001) by 6.5% and 7.8%. Significant, yet minor changes were also observed in the group C, where training in normoxia caused an increase (p<0.05) in relative values of WRmax by 2.8%, as well as an increase (p<0.05) in the absolute (1.3%) and relative (2.1%) values of VO2max. This data suggest that an intermittent hypoxic training protocol with high intensity intervals (4 to 5 x 4 min bouts at 90% of vVO2max-hyp) is an effective training means for improving aerobic capacity at sea level in basketball players.